Approaches to modeling occurrence of rolling contact fatigue damages in rails - S. M. Zakharov; E. V. Torskaya (Вестник Научно-исследовательского института железнодорожного транспорта)
Rolling contact-fatigue damages of rails along with their wear are the most common types of rail defects. In recent years, there have been significant changes in the distribution of rolling contact fatigue damages of rails especially on railways operating under heavy haul conditions.This paper is devoted to the overview of approaches to modeling of the occurrence of rolling contact fatigue (RCF) damages on working surfaces of rails. Four types of such approaches to modeling are considered. The first is based on the methods of contact mechanics. To realize it, the vehicle movement on the characteristic sections of the track is modeled, the forces acting in contact are determined, the contact problem is solved, and the values of the linear criterion of contact fatigue damage are determined. The required characteristics of rolling contact fatigue of the rail material are established on the basis of laboratory tests. The second approach uses the diagram of the adaptability of rail material to cyclic loads, proposed by K. Johnson, established on the basis of laboratory tests. The third approach uses criteria that have the physical meaning of the energy released at the contact as an index of the product of the tangential force in contact and relative slippage. In the fourth approach predicting the accumulation of plastic deformation under conditions of cyclic loading is performed on the basis of a series of standard tests of rail steels, including in the welded joint zone, and finite element modeling. In addition, there is also a probabilistic model, based on the assumption that it is possible to transfer the results of the RCF damage of rails on the experimental section of the road to any other site.As the conclusion the authors formulated directions for further studies on the formation and development of surface rolling contact fatigue defects in rails.